ADDRESSING FAMILY CAREGIVER BURDEN IN DIVERSE CARE SETTINGS AND POLICY IMPLICATIONS TO ATTENUATE CAREGIVER BURDEN. (11th November 2018) - Nam, S; Stratton, L
Abstract: Caregiving in the United States comprises multidimensional factors including diverse socioeconomic backgrounds, racial and ethnic groups, and care recipient needs. This symposium outlines findings using nationally representative datasets as well as data from a community-based program. Further, these studies draw attention to specific groups of family caregivers, such as African American caregivers, Latino immigrant caregivers, and spouses and adult-children, which are all in diverse caregiving situations. Caregiver burden largely varies depending on these different circumstances. This symposium will focus on addressing the variability of caregiver burden in diverse settings and attempt to provide suggestions on how to aid caregivers both at a community and public policy level. H. Moon will present on the interaction effects of care recipients' nativity status on the associations between race/ethnicity and caregivers' quality of life using data from the National Health and Aging Trends Study (NHATS) and the National Study of Caregiving (NSOC). K. Lee will address the importance of community cohesion for African American caregivers as a mean of accessible support in a longitudinal study using data from the Health and Retirement Study. S. Nam will explore the associations between types of caregiver burden and caregiver difficulties using the NHATS and NSOC data. L. Stratton will examine an Alzheimer's Association program in Iowa that aimed to help caregivers of people with dementia manage burden over time. Overall discussion will focus on implications for future policy and programs to help family caregivers and care recipients as well as ways to improve caregivers' health and well-being.